Cortical bone histomorphology of known‐age skeletons from the Kirsten collection, Stellenbosch university, South Africa. Issue 1 (11th February 2016) - Pfeiffer, Susan; Heinrich, Jarred; Beresheim, Amy; Alblas, Mandi
ABSTRACT: Objectives: Normal human bone tissue changes predictably as adults get older, but substantial variability in pattern and pace remains unexplained. Information is needed regarding the characteristics of histological variables across diverse human populations. Methods: Undecalcified thin sections from mid‐thoracic ribs of 213 skeletons (138 M, 75 F, 17–82 years, mean age 48 years), are used to explore the efficacy of an established age‐at‐death estimation method and methodological approach (Cho et al.: J Forensic Sci 47 (2002) 12‐18) and expand on it. The ribs are an age‐balanced sample taken from skeletonized cadavers collected from 1967 to 1999 in South Africa, each with recorded sex, age, cause of death and government‐defined population group (129 "Colored, " 49 "Black, " 35 "White"). Results: The Ethnicity Unknown equation performs better than those developed for European‐Americans and African‐Americans, in terms of accuracy and bias. A new equation based solely on the study sample does not improve accuracy. Osteon population densities (OPD) show predicted values, yet secondary osteon areas (On.Ar) are smaller than expected for non‐Black subgroups. Relative cortical area (Ct.Ar/Tt.Ar) is low among non‐Whites. Conclusions: Results from this highly diverse sample show that population‐specific equations do not increase estimate precision. While within the published range of error for the method (±24.44 years), results demonstrate a systematic under‐aging of young adults and over‐aging of older adults. The regression approach is inappropriate. The field needs fresh approaches to statistical treatment and to factors behind cortical bone remodeling. Am J Phys Anthropol 160:137–147, 2016. © 2016 The Authors American Journal of Physical Anthropology Published by Wiley Periodicals, Inc.